Photodynamic inactivation of prions by disulfonated hydroxyaluminium phthalocyanine - Janouskova, Olga; Rakusan, Jan; Karaskova, Marie; Holada, Karel (The Journal of general virology, 2012)
Sulfonated phthalocyanines (Pcs) are cyclic tetrapyrroles that constitute a group of photosensitizers. In the presence of visible light and diatomic oxygen, Pcs produce singlet oxygen and other reactive oxygen species that have known degradation effects on lipids, proteins and/or nucleic acids. Pcs have been used successfully in the treatment of bacterial, yeast and fungal infections, but their use in the photodynamic inactivation of prions has never been reported. Here, we evaluated the photodynamic activity of the disodium salt of disulfonated hydroxyaluminium phthalocyanine (PcDS) against mouse-adapted scrapie RML prions in vitro. PcDS treatment of RML brain homogenate resulted in a time- and dose-dependent inactivation of prions. The photodynamic potential of Pcs offers a new way to inactivate prions using biodegradable compounds at room temperature and normal pressure, which could be useful for treating thermolabile materials and liquids.
Keywords: Neurons; Cell Line; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Indoles; Time Factors; fotochemoterapie; mozek; tlak; Mice; Pressure; Brain; zvířata; Isoindoles; isoindoly; Temperature; Photochemotherapy; neurony; kyseliny sulfonové; časové faktory; myši; molekulární struktura; indoly; buněčné linie; priony; Prions; Sulfonic Acids; teplota; Molecular Structure; Animals